Смертельная кастрюля, или Возвращение Печенюшкина: повесть-сказка / Сергей Белоусов ; [художник Н. А. Фадеева] - Белоусов Сергей Михайлович (Эсби, 1993)
Экземпляры: Ф. 12 (20191022) / Инвентарный номер: 44676 / Цена: 28.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: Б 43 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)6-44